Before the sword - Lin, Grace (Los Angeles : Disney Press, 2020)
An original tale, inspired by legends of Mulan Hua and popularized by Disney. When her sister is bitten by a poisonous spider, Mulan travels with a healer to find a flower from which the antidote can be made to save her sister's life.
At head of title: Disney Mulan.
Includes bibliographical references (page [379]).
bt/ed
Keywords: Hua, Mulan -- (Legendary character) -- Juvenile fiction; Hua, Mulan -- (Legendary character) -- Fiction; Healers -- Juvenile fiction; Bites and stings -- Juvenile fiction; Sisters -- Juvenile fiction; Horses -- Juvenile fiction; Prophecies -- Juvenile fiction; Quests (Expeditions) -- Juvenile fiction; Healers -- Fiction; Bites and stings -- Fiction; Sisters -- Fiction; Horses -- Fiction; Prophecies -- Fiction; Quests (Expeditions) -- Fiction; China -- Juvenile fiction; China -- Fiction; Action and adventure fiction; Legends; Mythological fiction; Fantasy fiction